Investigating the Relationship between Social Skills and Social Acceptance with Academic Performance, Considering the Mediating Role of Ethical Privacy - Taghreed Radhi Abdol Mohsin; Hassan Ghalavandi (International Journal of Ethics and Society)
Introduction: Academic performance, as one of the most important criteria for evaluating students' ability to complete their studies, can grow under the influence of social skills, social acceptance, and respect for moral privacy. With the understanding of this importance, the present study was conducted with the aim of the relationship between social skills and social acceptance with academic performance, considering the mediating role of ethical privacy. Material and Methods: The research method was descriptive-correlation study. The statistical population consisted of 645 middle school students of Babol province, using Cochran's formula, 347 of them were selected by one-stage cluster random sampling method. Four standard questionnaires of social skills, social acceptance, respect for moral privacy, and academic performance were used for gathering data. The face and content validity of the questionnaire was confirmed by experts and through factor analysis. The reliability of the instrument was confirmed using Cronbach's alpha coefficient. Data analysis was done using Pearson's correlation coefficient and path analysis in SPSS and Lisrel statistical software. Results: The results showed that the relationship between social skills and social acceptance with students' academic performance was positive and significant, and the mediating role of ethical privacy in the relationship between social skills and social acceptance with students' academic performance is positive and significant. Conclusion: Based on the results; in order to increase academic performance, it is possible to increase the social skills and ability of social acceptance of students in the context of respecting moral privacy.